2018
DOI: 10.1007/s11367-018-1517-x
|View full text |Cite
|
Sign up to set email alerts
|

LCA of aquaculture systems: methodological issues and potential improvements

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 85 publications
(71 reference statements)
0
48
0
3
Order By: Relevance
“…type of culture, cultured species or geographical location) and the lessons learned from the study were extracted and categorized. The current review focuses on the two latter aspects, as an analysis of the LCA methodological aspects of the studies is the focus of another paper (Bohnes & Laurent ). Nonetheless, some central methodological aspects of importance for the analysis of the findings (like the functional unit) are also addressed here.…”
Section: Review Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…type of culture, cultured species or geographical location) and the lessons learned from the study were extracted and categorized. The current review focuses on the two latter aspects, as an analysis of the LCA methodological aspects of the studies is the focus of another paper (Bohnes & Laurent ). Nonetheless, some central methodological aspects of importance for the analysis of the findings (like the functional unit) are also addressed here.…”
Section: Review Methodologymentioning
confidence: 99%
“…We chose to harmonize the cases based on the live‐weight product quantity because of the large amount of studies using this type of functional unit (78%). The relevance of such a functional unit is discussed in a follow‐up paper, focusing on methodological aspects (Bohnes & Laurent ). It is worth noting that no further harmonization of the results was performed (e.g.…”
Section: Review Methodologymentioning
confidence: 99%
“…A large percentage of currently published studies use greenhouse gas emissions (CO 2 E) as the sole comparable environmental impact category considered, while also quantifying considerations such as energy and water consumption. Bohnes and Laurent (2019) reviewed LCAs of aquaculture studies and found that in 98% of the studies CO 2 E was utilized as an impact category, whereas abiotic depletion was applied in only 22% of the studies published. Although a portion of the literature includes other impact categories, such as acidification, eutrophication, and abiotic depletion (fossil fuels) (Hindelang et al 2014;Cohen et al 2018;Maucieri et al 2018).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Although a portion of the literature includes other impact categories, such as acidification, eutrophication, and abiotic depletion (fossil fuels) (Hindelang et al 2014;Cohen et al 2018;Maucieri et al 2018). Bohnes and Laurent (2019) reviewed LCAs of aquaculture studies and found that in 98% of the studies CO 2 E was utilized as an impact category, whereas abiotic depletion was applied in only 22% of the studies published. Questions have also been raised as to whether the currently utilized suites of impact categories capture critical aspects of seafood production, such as resource depletion due to overfishing for forage fish (Froehlich et al 2018).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…While some salmonid aquaculture LCA publications include the farm-level energy use, few of them give a breakdown of the total electricity use at the most important subprocess level. As emphasized in a recent review of LCA on aquaculture systems by Bohnes and Laurent (2018), one future need of aquaculture LCAs is to construct aquaculture life cycle inventory (LCI) databases with a special need for developing countries. This paper presented the results of LCI and life cycle impacts of Atlantic salmon (S. salar) harvested in a commercial-scale indoor RAS farm in northern China.…”
mentioning
confidence: 99%